Toll-like receptor (TLR) 2 and TLR13 from the endangered primitive-ray finned fish Dabry’s sturgeon (Acipenser dabryanus) and their expression profiling upon immune stimulation - Rong Tang; Sisi Wang; Panpan Han; Qihuan Zhang; Shuhuan Zhang; Xiaoping Xing; Rong Shao; Wei Xu; Qiaoqing Xu; Qiwei Wei; Zhitao Qi (Aquaculture Reports, 2020)
Toll-like receptors (TLRs) are important pattern recognition receptors (PRRs) which can recognize a series of pathogen associated molecular patterns (PAMPs) to initiate the host innate immune responses. In the present study, two TLRs (TLR2 and TLR13) were identified for the first time from the endangered primitive-ray finned fish Dabry's sturgeon (Acipenser dabryanus), a critically endangered species. The full-length of sturgeon TLR2 was 2591 bp, including an open reading frame (ORF) of 2394 bp which encoded a polypeptide of 797 amino acids. The full-length adaTLR13 cDNA was 3648 bp, consisting of an ORF of 2889 bp which encoded a polypeptide of 962 amino acids. Both TLRs shared high sequence identity/similarity with their counterparts from other fish species. In addition, both TLRs contained typical TLRs motifs, including a signal peptide, eight LRRs, an LRR-CT domain in the extracellular N-terminal, a transmembrane domain, and a C-terminal intracellular TIR domain. Realtime qPCR assays showed that both were ubiquitously detected in all examined tissues, but exerted different expression patterns. Following LPS and polyI:C stimulation, both TLRs were up-regulated in head-kidney primary leucocytes, indicating that both TLRs might involve in recognizing LPS and polyI:C. To the best of our knowledge, this is the first report about the gene structure and expression of TLR2 and TLR13 in Dabry's sturgeon. Our results enriched the repertoire of TLRs of Dabry’s sturgeon and provided the basis for understanding the functional evolutionary history of vertebrates` TLRs. Keywords: Acipenser dabryanus, Toll-like receptors, Gene clone, LPS, PolyI:C